2013
DOI: 10.1091/mbc.e12-12-0895
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane domains enriched in cortical endoplasmic reticulum function as membrane protein trafficking hubs

Abstract: This study investigates the hypothesis that trafficking of membrane proteins occurs at plasma membrane (PM) domains adjacent to underlying cortical endoplasmic reticulum (cER). The authors observe exocytosis of transferrin receptor and vesicular stomatitis virus G-protein to occur preferentially (>80%) at cER-enriched PM domains. They also report a preferential (>80%) localization of clathrin-coated pits at these domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 57 publications
(38 reference statements)
2
36
0
1
Order By: Relevance
“…Early electron microscopy analyses of Kv2.1 immuno-gold labeling in the hippocampus have indicated that Kv2.1 clusters localize above SSCs that are juxtaposed to astrocytic processes (Du et al, 1998), and fluorescence microscopy analyses of live cultured cells shows that Kv2.1 clusters reside atop projections of the ER that terminate near the plasma membrane -i.e. cortical ER (cER) (Fox et al, 2013a). Consistent with these observations, Kv2.1 clusters on the soma and axon initial segment partially colocalize with ryanodine receptors (RyRs) in culture and in the intact brain (King et al, 2014;Lim et al, 2000;Mandikian et al, 2014).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…Early electron microscopy analyses of Kv2.1 immuno-gold labeling in the hippocampus have indicated that Kv2.1 clusters localize above SSCs that are juxtaposed to astrocytic processes (Du et al, 1998), and fluorescence microscopy analyses of live cultured cells shows that Kv2.1 clusters reside atop projections of the ER that terminate near the plasma membrane -i.e. cortical ER (cER) (Fox et al, 2013a). Consistent with these observations, Kv2.1 clusters on the soma and axon initial segment partially colocalize with ryanodine receptors (RyRs) in culture and in the intact brain (King et al, 2014;Lim et al, 2000;Mandikian et al, 2014).…”
Section: Introductionsupporting
confidence: 57%
“…The majority of experiments utilizing light microscopy were performed using TIRF microscopy to restrict illumination to within ∼100 nm of the basal surface of the cell in order to visualize the cER (Fox et al, 2013a). Transfected HEK cells and neurons were imaged with a Nikon Eclipse Ti Perfect-Focus equipped TIRF/widefield fluorescence microscope equipped with AOTF controlled 405, 488, 543 nm diode lasers, 100 mW each, and an Intensilight wide-field light source.…”
Section: Tirf Microscopymentioning
confidence: 99%
“…3D,F), suggesting that the decreased current density displayed by the LQT5 mutant does not seem to be accounted for by trafficking defects. However, TIRF does not allow discrimination between the signals from the plasma membrane and those arising from the cortical ER, which is especially relevant for some K + channels (Fox et al, 2013). Thus, an effect on trafficking cannot be totally excluded.…”
Section: C-terminusmentioning
confidence: 99%
“…In this model, the cytoskeleton and its associated proteins establish diffusion barriers, and the energy-dependent constant delivery and removal of membrane proteins and lipids at the plasma membrane creates lateral variations in component abundance (Gheber and Edidin, 1999; Turner et al, 2005; Lavi et al, 2007; Fan et al, 2010). Indeed, localized trafficking hubs in the plasma membrane have been shown to produce stable domains of distinct protein compositions (Deutsch et al, 2012; Fox et al, 2013). Whether the sphingolipid domains in the plasma membrane are local hubs for sphingolipid trafficking might be assessed by performing high-resolution SIMS in a depth profiling mode to produce three-dimensional images of the intracellular sphingolipid distribution (Yeager et al, 2016).…”
Section: Implications For Plasma Membrane Organization Hypothesesmentioning
confidence: 99%